Foliar damage by adults of spring weevils (Coleoptera: Curculionoidea) on Quercus species from Mediterranean oak forests in the Iberian Peninsula - Gallardo, Patricia; Cárdenas, Ana (Entomologica Fennica, 2017)
This paper describes the feeding damage by adults of spring leaf-eating weevils (Coleoptera: Curculionoidea) colonizing the canopies in Mediterranean oak forests in southern Iberian Peninsula. The weevils, captured by the beating tree-top method, belonged to nine species of Curculionoidea. To describe their respective damage, feeding studies were performed by supplying leaves of Quercus ilex and Q. suber as food. To each beetle, one hardened leaf and one sprout of each oakplant species were supplied for knowing differences in feeding damage related to age of leaves. The essaywas performed with eight replicates for each weevil species. Three of the nine species caught did not feed and eventually died during the experiment. The observations indicate that the most of the species can consume indifferently leaves of Q. ilex and Q. suber and that hole-feeding and skeletonising were the most common damage.